PENANAMAN KARAKTER PEDULI SOSIAL DI SMP NEGERI 10 PALEMBANG - Eka Febriyanti; Fajri Ismail; Syarnubi Syarnubi (Jurnal PAI Raden Fatah, 2022)
This research is based on the observation that some students have not carried out social care activities for example, such as in activity although inactivities activities are carried out e day, students have not yet conducted such social care activities. So to instill socialcharacteristicteachers in tincinactivitiesher students, school citizens and parents must work together so that students are embedded in socisociale characters both inside and outside of school. This study aims to determine Knowing Planting Social Care Characters in SMP Negeri 10 Palembang. This type of research is qualitative research that is the informant is the principal, teachers, school residents, students, and parents of students. Data collection techniques in this study were observation, interviews, and documentation. While data analysis techniques are using data reduction, data presentation, and verification/conclusion drawing. The results of data research using interviews that obtained the results of the analysis are the planting of social care characters in SMP Negeri 10 Palembang through the habituation program by getting students accustomed to being active every day, conditioning is the school putting up posters relating to social care characters and exemplary examples by school principals, teachers, and school residents.